Globalization and small businesses - Katsuhiko Hirasawa (OrdnungsPolitisches Portal (OPO), 2019)
The purpose of this paper is to examine what kind of impact neo - liberalisti c globali za- tion has on small businesses in Japan. First, we review the background of neo - liberal- istic globalization. It can truly be said that globalization not only results in the overseas development of goods and capital, it is also closely linked to new li beralism and dereg- ulation . Then we examine how small businesses in Japan have changed. It may be true that the existence of small businesses, which had been built in a self - sufficient manner within Japan, was reorganized in a wider East Asian region, we should not overlook that the advancement of globalization has changed the struc ture of small businesses established in Japan. Thus, we clarify the impact of neo - liberalistic global- ization on small busi ne sses. As can be shown more than 1 - million small businesses closed or went bankrupt in 15 years, during which globalization gained ground. Whereas the overseas expansion of the econ omy had an impac t on the national econ- omy, globalization today progresses via fierce competition based on neo - liberalism in the background of the declines in the rates of profit and the amounts of profit of Amer- ican big businesses. This neo - liberalistic globalization caus es the industry structure of each country to be reor ganized, and it causes the sustainment of small businesses to fail.
Keywords: 330; Globalization; SME; Japan